Analisis Pengaruh Media Sosial, Keterlibatan Pengunjung dan Pengalaman Pariwisata Yang Berkesan Terhadap Niat Berkunjung Kembali yang Dimediasi oleh Citra Destinasi dan Kepuasan Pengunjung (Studi Pada Objek Wisata di Kabupaten Bantul) - Pratiwi, Melinda Putri; Astuti, Budi (Universitas Hamzanwadi, 2025)
This study generally aims to determine whether there is an influence of social media variables, destination image, visitor involvement, visitor satisfaction, and memorable tourism experiences on the intention to revisit tourist destinations in Bantul Regency. Quantitative research based on primary data with respondents who visited tourist destinations in Bantul Regency. Respondents numbered 225 people, obtained through convenience sampling techniques. The results of the study showed that social media has a positive and significant effect on destination image and intention to revisit, and the destination image variable is positively able to mediate social media with the intention to revisit. In addition, destination image has a positive and significant effect on visitor satisfaction and intention to revisit. Visitor satisfaction has a positive and significant effect on the intention to revisit, and is able to mediate visitor involvement with the intention to revisit and is also able to mediate memorable tourism experiences with the intention to revisit. Other findings show that visitor involvement has a positive and significant effect on visitor satisfaction, but visitor involvement does not affect the intention to revisit, while memorable tourism experiences have a positive and significant effect on visitor satisfaction and intention to revisit. These findings are expected to be used by tourism managers to determine future marketing strategies